Hakim dan Objek Hukum: Telaah Teoritis tentang Pengertian, Fungsi, dan Syarat-Syarat dalam Kajian Ilmu Hukum" - Wika Yunisa Fathonah; Cahaya Cahaya (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
judge is a state judicial official who has the authority to adjudicate and enforce the law. Meanwhile, the object of law is anything that can be of legal interest to a legal subject. This article aims to explain the meaning of a judge, the meaning of a legal object, and the requirements for a legal object. The research method used is a literature study with a normative approach. The results of the study indicate that judges play a strategic role as interpreters of the law, while legal objects must meet certain requirements to be legally valid. This research confirms that a deep understanding of judges and legal objects is important in judicial practice. This paper discusses basic concepts in Islamic law that include the definition of a judge, legal objects, legal subjects, and the requirements for both. In addition, this study also touches on Undang-Undang Nomor 48 important terms such as mukallaf, ahliyyatu al-wujub, and ahliyyatu al-ada". The purpose of this study is to understand the position of a judge as a lawmaker, the position of humans as legal subjects, and what can be an object of law. The research method used is a literature study with a normative-theoretical approach. The results of the study show that in Islamic law, the judge is Allah as the maker of the law, the subject of the law is a human being who has legal eligibility (ahliyyah), while the object of law is everything that is the target of the law, with certain conditions determined by the Shari'a.